Implementing a multi-modal support service model for the family caregivers of persons with age-related macular degeneration: a study protocol for a randomised controlled trial. Issue 8 (4th August 2017) - Gopinath, Bamini; Craig, Ashley; Kifley, Annette; Liew, Gerald; Bloffwitch, Jaye; Vu, Kim Van; Joachim, Nichole; Cummins, Rob; Heraghty, Julie; Broady, Timothy; Hayes, Alison; Mitchell, Paul
Abstract : Introduction: Age-related macular degeneration (AMD) is a leading cause of blindness and low vision among older adults. Previous research shows a high prevalence of distress and disruption to the lifestyle of family caregivers of persons with late AMD. This supports existing evidence that caregivers are 'hidden patients' at risk of poor health outcomes. There is ample scope for improving the support available to caregivers, and further research should be undertaken into developing services that are tailored to the requirements of family caregivers of persons with AMD. This study aims to implement and evaluate an innovative, multi-modal support service programme that aims to empower family caregivers by improving their coping strategies, enhancing hopeful feelings such as self-efficacy and helping them make the most of available sources of social and financial support. Methods and analysis: A randomised controlled trial consisting of 360 caregiver–patient pairs (180 in each of the intervention and wait-list control groups). The intervention group will receive the following: (1) mail-delivered cognitive behavioural therapy designed to improve psychological adjustment and adaptive coping skills; (2) telephone-delivered group counselling sessions allowing caregivers to explore the impacts of caring and share their experiences; and (3) education on available community services/resources, financial benefits and respite services. The cognitive behavioural therapy embedded in this programme is the best evaluated and widely used psychosocial intervention. The primary outcome is a reduction in caregiver burden. Secondary outcomes include improvements in caregiver mental well-being, quality of life, fatigue and self-efficacy. Economic analysis will inform whether this intervention is cost-effective and if it is feasible to roll out this service on a larger scale. Ethics and dissemination: The study was approved by the University of Sydney human research ethics committee. Study findings will be disseminated via presentations at national/international conferences and peer-reviewed journal articles. Trial registration number: The trial registration number is ACTRN12616001461482; pre-results.